Mechanics of Question Paper Setting - Reddy, K R (Journal of Gandaki Medical College-Nepal, 2018)
The goal of medical education is to produce the physician we would like to see if we are sick - Melinkoff In all educational developments, one of the most troublesome questions is that of evaluation. Written examination is the most widely used tool in evaluation and assessment of the competency of the medical students. At present, questions are prepared casually just before the examination and are not subjected to any quality check, which may lead to confusion or wrong understanding of the questions by the students. This article is aimed at providing guidelines and a scientific method to frame good question papers to improve the quality of evaluation and assessment of medical students. J-GMC-N | Volume 11 | Issue 01 | January-June 2018, Page: 64-67